Development Of Web-Based E-Learning On Design Of Experiment Technique; Case Of Randomized Complete Block Design (RCBD) - Muhd. Nordin, Nor Ilyana (Universiti Sains Malaysia, 2005)
In research and development, often half of the resources are spent on solving optimization problems. With the rapidly rising costs of making experiments, it is essential that the optimization is done with as few experiments as possible. This is one important reason why Design of Experiments (DOE) is needed. In certain field there are circumstances in which the experimenter would like to screen factors to decide which are the most important. In these situations the engineering model of DOE is useful. These all signify the importance of DOE. Randomized Complete Block Design (RCBD) and Latin Square Design are DOE blocking techniques. This project has a vision of educating its viewer through a different environment of learning the subject of RCBD and Latin Square Design. Materials are explored from various resources that can be found in books and in the internet just to ensure the webpage provide sufficient and refer to reliable information. It proved that the materials included in the webpage combines all resources so that the webpage is ensured to cover entire concept behind both topics. With interactive links to relate one slide to the other, viewers are directed clearly from one page to the other until they have covered the whole topics in RCBD and Latin Square Design that stated in the research scope. Besides, there are also sections to test the understanding of the viewer that are named after “Do It Yourself”. In this section, complete solutions are provided for each problem, so that the viewer can check their solution with the solutions provided in the webpage. Other than learning, there are also slides provided for relaxations that are named after “Take 5”. These slides provide refreshment for viewers because its contents can lighten up their mind. Moreover, the overall structure of the webpage is well organized and viewers are ensured not to getting lost while surfing the webpage. The whole webpage design, development and its content are arranged in a way that is hoped to facilitate and add up to viewers’ awareness of the concept behind the application of RCBD and Latin Square Design. Above all, the webpage is expected to give new and clear lessons for those who are not familiar with the subject and also add up to current knowledge of the subject for those who familiar with the subject. It is also hoped that the webpage can be recommended as one of the useful resources for RCBD and Latin Square Design.